Implementation of medication management services at the primary healthcare level – a pilot study - Brajković Andrea; Mucalo Iva; Vidović Toni; Gonzaga Mariana Martins; Nascimento Do; Balenović Antonija; Protrka Ino; De Oliveira Djenane Ramalho (Acta Pharmaceutica)
This study employed a mixed-method approach to enable the implementation of comprehensive medication management (CMM) services in Croatia’s primary care setting. Drug therapy problems (DTPs) and factors associated with their occurrence were determined in patients with chronic diseases from January 2018 to April 2019. The pre-implementation stage established the foundations for the early implementation stage, in which the practice was set up, the patients’ recruitment initiated and various challenges identified. During the study period, 86 patients were recruited for CMM provision. Overall, 2.8 DTPs (± 1.6) per patient were identified and the majority (96.2 %) presented with at least one DTP. Multiple regression analysis showed that type 2 diabetic patients (p = 0.025) and patients using five or more medications (p = 0.011) should be prioritized to receive CMM services as potentially they have a higher number of DTPs, and could, therefore, obtain a greater benefit from the service.